Uniform Attractors for Nonclassical Diffusion Equations with Memory - Yongqin Xie; Yanan Li; Ye Zeng (Journal of Function Spaces)
We introduce a new method (or technique), asymptotic contractive method, to verify uniform asymptotic compactness of a family of processes. After that, the existence and the structure of a compact uniform attractor for the nonautonomous nonclassical diffusion equation with fading memory are proved under the following conditions: the nonlinearity f satisfies the polynomial growth of arbitrary order and the time-dependent forcing term g is only translation-bounded in Lloc2(R;L2(Ω)).